Reading Comprehension through Multimodal Literacy Approach for English Education - Daulay, Ernita; Utami Dewi (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
In the digital era, reading comprehension of multimodal texts that integrate written language with images, videos, and interactive elements has become crucial yet challenging for many students. This mixed-methods study investigated the effectiveness of a multimodal instructional approach in enhancing reading comprehension among 120 Indonesian high school students. The quantitative component employed a quasi-experimental design with pre/post reading comprehension tests, while the qualitative component utilized observations and interviews. The results revealed that the experimental group receiving multimodal instruction achieved significantly higher reading comprehension scores compared to the control group receiving traditional text-based instruction (F(1, 117) = 12.68, p < .001, ηp2 = .098). The multimodal approach was particularly beneficial for students with lower initial reading proficiency levels. Qualitative data indicated increased engagement, motivation, comprehension facilitation, accommodation of diverse learning styles, and the need for technology integration support and instructional scaffolding. The findings align with multimedia learning theory and differentiated instruction principles, providing empirical evidence supporting the integration of multimodal elements to create engaging, accessible, and effective reading experiences. Implications for teacher professional development, curriculum design, and future research directions are discussed. Overall, this study contributes to the growing literature on multimodal literacy pedagogy and offers practical insights for enhancing reading instruction in the 21st century multimedia landscape.